Freestyle: Breathe early - Mills, G. (Swimming Technique, 2005)
Breathing early and long during the stroke cycle allows you to grab as much air as possible on each breath. With all that good air in your lungs, making its way to the blood cells, you'll have the fuel necessary to keep your splits from dropping off, that is, of course, if you've trained correctly!